Inventory of Simplisia of Medicinal Plants Traded in Bogor Traditional Market - Indah Ayu Kusuma; Eliza Nur'Aini; M Sabta Nugraha; Insan Kurnia (Jurnal Biologi Tropis, 2023)
Until now, many people still use plants as ingredients for traditional medicine. The production of medicinal plants as raw materials for traditional medicine has also continued to increase. This study aims to identify the types of plant simplicia that are traded in the traditional market in Bogor City. The research was carried out in January 2023 by surveying all traders in all traditional markets in Bogor City. The results of the study found seven sellers of plant simplicia in three traditional markets, namely Anyar Market, Gunung Batu Market and Warung Jambu Market. There were no plant simplicia traders in the other seven markets. There were 76 species of plant simplicia found from 38 families. The family with the most number of species is Zingiberaceae with 15 species. Habitus of plant simplicia consists of seven types which are dominated by herbaceous (44%). The plant simplicia part that is used consists of 13 kinds which are dominated by the leaves (16 species). The use of plants simplicia is known for 32 kinds of medicinal treatment. The most widely used form is the treatment of the digestive tract (37 species). Six species of plant simplicia have status according to both CITES and IUCN.  Plant simplicia is sold at various prices.  Plant simplicia is sold for a fruit unit, a bundle, a pack, or a kilogram with prices ranging from IDR 5,000 to IDR 300,000.00.